Device-to-Device Communication Based IoT System: Benefits and Challenges. Issue 4 (4th July 2019) - Pawar, Praveen; Trivedi, Aditya
ABSTRACT: Autonomous computing, communication, and collaboration among devices have their importance to transform the digital world. Emerging technology device-to-device (D2D) communication has a great impetus to facilitate peer-to-peer network. Therefore, D2D communication technology is expected to be an essential part of the Internet of Things (IoT). Rapid growth in quality of service demand leads to fundamental changes in the architecture of IoT system. This paper explains the benefits and challenges for intelligent D2D communication that will be required to accomplish the requirements for IoT. Many industries and standardization bodies have shown enormous interest towards the implementation of D2D approach in wireless networks. D2D approach facilitates to work without the essential control of the centralized supervision which makes wireless networks more spectrum and energy efficient with traffic offloading. Inter-networking devices offer various applications towards the development of IoT. Physical constraints of the devices and resource constraints of the networks give rise to several issues which need to be resolved. Here, we review the current status in the advancement of D2D technology subject to resources utilization, routing techniques, and interference management. Moreover, potential future challenges are explored that may be faced by the scientific community.